(untitled) (Journal of Nobel Medical College, 2014)
Objective: To evaluate the clinical profile of patients with gallbladder cancer. Methodology: This is a single institution based retrospective study of patients with gallbladder cancer who presented at College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. Patients presenting during the two years period from August 2011 to July 2013 were reviewed. Result: Out of 12 patients, 9 were females (75%) and 3 were males (25%), showing female preponderance. Most of the patients (75%) were in age group of 51-70 years. Only one patient (8%) was below 50 years of age. Main symptom was pain associated with anorexia, nausea & vomiting. Major signs were palpable mass, hepatomegaly and jaundice. All the histopathological reports were adenocarcinoma. 8 patients (66.66%) presented with advanced disease and were managed with extended cholecystectomy followed by systemic chemotherapy. Conclusions: Prevalence of gall bladder cancer is higher in females in our series. Most of the patients were in fifth to seventh decade of life and presented in advanced stage. Gallbladder cancer showed association with gallstones. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10050 Journal of Nobel Medical College Vol.3(1) 2014; 27-30